Association Between No‐Flow Time, Prehospital Low‐Flow Time, and Conversion to Nonshockable Rhythm in Patients With Out‐of‐Hospital Cardiac Arrest Presenting With Initial Shockable Rhythm: A Nationwide Prospective Study in Japan - Kenji Kandori; Satoshi Nakajima; Tasuku Matsuyama; Tetsuhisa Kitamura; Hiromichi Narumiya; Masahito Hitosugi; Yohei Okada (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Out‐of‐hospital cardiac arrest (OHCA) with initial shockable rhythm generally has a favorable prognosis. However, the prognosis worsens when this rhythm transitions to nonshockable rhythm on hospital arrival. This study aimed to investigate the association between no‐flow time (NFT), prehospital low‐flow time (LFT), and the conversion to nonshockable rhythm on hospital arrival in patients with OHCA initially exhibiting shockable rhythm. Methods We analyzed adult patients with OHCA from the JAAM‐OHCA (Japanese Association for Acute Medicine Out‐of‐Hospital Cardiac Arrest) registry (June 2014–December 2020) with initial shockable rhythm. The primary outcome was rhythm conversion to nonshockable on hospital arrival. Adjusted odds ratios (aORs) with 95% CIs were calculated using a logistic model to examine the associations between NFT, prehospital LFT, and rhythm conversion. Results Of 68 110 patients, 3720 patients were included in our analysis. On hospital arrival, 27.9% patients achieved return of spontaneous circulation, 32.8% maintained shockable rhythm, and 39.3% transitioned to nonshockable rhythm (718 to pulseless electrical activity, 744 to asystole). Median NFT was 4 minutes (interquartile range [IQR], 1–9 minutes), and median prehospital LFT was 22 minutes (IQR, 14–31 minutes). Longer NFT and prehospital LFT were associated with higher aORs of rhythm conversion: NFT (5–9 minutes: aOR, 1.38 [95% CI, 1.14–1.67]; ≥10 minutes: aOR, 1.75 [95% CI, 1.44–2.14]); and prehospital LFT (15–19 minutes: aOR, 2.56 [95% CI, 2.00–3.27]; 20–29 minutes, aOR, 4.73 [95% CI, 3.83–5.85]; ≥30 minutes, aOR, 6.85 [95% CI, 5.49–8.56]). Conclusions Prolonged NFT and prehospital LFT were significantly associated with rhythm conversion to nonshockable on hospital arrival in patients with OHCA with initial shockable rhythm at the scene.